The palace of Samosata - Wouter Kruijer, Lennart, 1989- (Bonn)
xviii, 303 sayfa, 98 sayfa resim, plan
Keywords: “Volume 103 offers an innovative analysis of cultural transformation in Hellenistic and early-Roman Samosata, the capital of Commagene, where a large and lavishly decorated palatial structure was excavated in the 1980s. On the basis of a detailed investigation of object change in this West Asian locality, the book’s main aim is to engage with broader questions about the impact of increased Afro-Eurasian connectivity during the 4th c. BCE – 1st c. CE. Drawing on globalization theory and the concept of ›objectscapes‹, it develops a methodological alternative to the persistent yet reductive notion of ›Hellenism in the East‹. These broader themes are embedded in a thorough archaeological analysis of the late-Hellenistic palace, unlocking archaeological legacy data – particularly its architectural decoration and sculptural fragments – that greatly expand our knowledge of the broader Commagenian objectscape.” --